2013
DOI: 10.1002/glia.22578
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor couples Rac1-GEF Tiam1 to direct oligodendrocyte precursor cell migration

Abstract: Oligodendrocyte precursor cells (OPCs) originate from restricted regions of the brain and migrate into the developing white matter, where they differentiate into oligodendrocytes and myelinate axons in the central nervous system (CNS). The molecular mechanisms that orchestrate these long distance trips of OPCs to populate throughout the CNS are poorly understood. Emerging evidence has argued the expression of N-methyl-d-aspartic acid (NMDA) receptors (NMDARs) in oligodendrocyte lineage cells in vivo, but their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 115 publications
(203 reference statements)
2
32
0
Order By: Relevance
“…The results showed that the numbers of Olig2/BrdUdouble-positive cells are unchanged in the SVZ but are reduced in the Fim and CC in the N-Arf6-CKO mice. These results led to the conclusion that neuronal Arf6 plays an important role in OPC migration from the SVZ to the Fim and CC but not in NSC proliferation/differentiation, consistent with reports that OPCs differentiated from NSCs in the SVZ migrate to target areas in the postnatal brain [19][20][21][22][23] . However, it is still possible that proliferative NSCs in brain regions other than the SVZ differentiate into OPCs that migrate to the Fim and CC.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the numbers of Olig2/BrdUdouble-positive cells are unchanged in the SVZ but are reduced in the Fim and CC in the N-Arf6-CKO mice. These results led to the conclusion that neuronal Arf6 plays an important role in OPC migration from the SVZ to the Fim and CC but not in NSC proliferation/differentiation, consistent with reports that OPCs differentiated from NSCs in the SVZ migrate to target areas in the postnatal brain [19][20][21][22][23] . However, it is still possible that proliferative NSCs in brain regions other than the SVZ differentiate into OPCs that migrate to the Fim and CC.…”
Section: Discussionsupporting
confidence: 90%
“…Characteristically, OPCs are motile cells which can migrate long distances and continuously survey their environment via extended filopodia (Hughes et al, 2013). The activation of both AMPA/kainate and NMDA receptors in OPCs has been shown to increase motility through the modulation of the adhesion molecule PSA-NCAM or the modification of Tiam1 signalling, which induces lamellipodium growth of leading OPC processes (Xiao et al, 2013). AMPA/kainate receptor activation also leads to the composition of an α v -integrin and proteolipid protein (PLP) complex which associates with the AMPA receptor subunit GluA2 -a subunit which makes AMPA receptors impermeable to calcium (Gudz et al, 2006; see Figure 2).…”
Section: Glutamate and Opc Migrationmentioning
confidence: 99%
“…Several studies have later addressed the importance of Ca 2þ signalling in process extension and OPC migration [58][59][60][61][62], in their differentiation, myelination and re-myelination capacity [63 -66], and in retraction of membrane sheaths and cell death in mature mouse oligodendrocytes [67].…”
Section: Oligodendroglial Precursor Cells (Ng2-glia)mentioning
confidence: 99%